Pengaruh Modal Kerja dan Biaya Produksi Terhadap Pendapatan - Nurul Fitriyani; Sulistia Suwondo (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research is motivated by the decline in income during last three years and the ineffective management of working capital and production costs at CV Samasta Mitra. So it is worried that it will affect the income of the company and business development. This research aims to examine the effect of working capital and production costs on income at CV Samasta Mitra. The data used in this study is time-series data with a monthly scale starting from 2018 to 2020. The research method used is a quantitative method using IBM SPSS Statistics 25 assistance. The analysis technique used in this study is multiple regression analysis. The results of this study indicate three of the hypothesis proposed, so that the results obtained both partially and simultaneously, working capital and production costs have a positive and significant effect on the income of CV Samasta Mitra.